Migrant-Background Student Experiences of Facing and Overcoming Difficulties in Finnish Comprehensive Schools - Mervi Kaukko; Jenni Alisaari; Leena Maria Heikkola; Nick Haswell (MDPI AG, 2022)
This article considers what students with a migrant background in Finnish comprehensive schools report as difficult, and how they succeed in overcoming these difficulties. We draw on two sets of school wellbeing and learning surveys for migrant students, conducted in 2016 and 2021 in comprehensive schools (grades 1-9) in and around two major cities in Finland. We pay attention to student answers to three questions: What is difficult in school? How do you succeed in difficult tasks in school? and Who helps you in school? The datasets from the two points in time are compared to see whether changes in school demographic situation and the student length of stay in Finland had an impact on student experiences. Our findings show that theory-based school subjects that depend strongly on language, such as science subjects, maths, Finnish, Swedish and English, are considered difficult. Additionally, interaction with peers, which also relies on language, causes challenges. The students report turning to teachers, other professionals and peers for assistance and support, and also mention personal strategies they have developed to overcome school-related difficulties. Understanding what migrant students find difficult, as well as how, and with the help of whom, they overcome such difficulties is crucial for the development of effective and sensitive pedagogical practices.